Celebrating UNAM-Oshakati Campus health day/world health day: a community service: professional and personal life experiences - Pinehas, Lusia N. Ndahambelela; Shifiona, NN.; Shikongo, KKI. (International Journal of Advanced Nursing Studies, 2014)
Background: The University of Namibia-Oshakati Campus has a tradition to celebrate UNAM Health Day which coincided with the World Health Day annually. The day had always been celebrated within the Oshakati Campus premises. Nurse lecturers from the School of Nursing and Public Health always decide on the activities of the day and they volunteered themselves to take part in the event. The activities conducted were such as blood pressure monitoring, taking of weigh and giving general health education on different topics. In that case activities only catered for the University’s staff members, some students and few distance students and individuals who might find them visiting the campus during that day. This year (2013), lecturers celebrated UNAM/World day on the 04th April and they decided to move out of the campus to the nearby “open market” community to sell their service and to raise awareness about the reality of diseases such as hypertension, diabetes mellitus, and obesity under the theme: “High blood pressure” (WHO’s theme of the year). The “open market” is a place in Oshakati (Oshana region) in the northern Namibia where many self-employed local small- and medium business people, males and females gather to sell local food and some “okapana” (takeaways) to passerby. Aim: The aim is to take the service to the community around Oshakati to sell their service and to raise awareness about the reality of diseases such as hypertension, diabetes mellitus, and obesity under the theme: “High blood pressure”. Method: No actual research was done. The service was carried out in April 2013. Results: No actual data analysis was done. The analysis of the findings was based on the users of the services. Many people who used the services were found to have high blood pressure up to 229/124mmHg, many of the women who sell “okapana” are overweight and seem to have lack the knowledge about balanced diet because they could not understand why they are overweight compared to their Body Mass Index (BMI). They prefer to keep their “fatness” because if they lose weight they will be laughed at and said to have AIDS. Many people were found to have high blood glucose levels (33.3mmol/L). Conclusion: The results indicate the need for health care providers to strengthen the community services and outreach to improve the knowledge and understanding of community members on the need for undergoing regular screening. Keywords: Blood Glucose Level, Health Education, High Blood Pressure, Body Mass Index, Obesity.